Stability of risk attitudes and media coverage of economic news - Franziska Tausch; Maria Zumbuehl (Max Planck Institute for Research on Collective Goods, 2016)
This paper investigates the impact of exogenous changes in individuals' perceived economic environment on their self-stated risk attitudes by exploiting changes in media coverage of economic news. We use information on risk attitudes from the German Socioeconomic Panel and combine it with data on the average daily frequency of economic news reports during the year and the month preceding the date of the risk attitude elicitation. Using fixed effects regressions we observe effects of both long and short term changes in the media. We find that an increase in economic news in the previous year, irrespective of whether the news are bad or good, is negatively related to individuals' willingness to take risks. An increase in news that are aggregated over the previous month, however, relates to a decrease in risk aversion if the news are predominantly good. The strength of the relations depends on individuals' personal characteristics and personality traits. A positive correlation between bad news coverage and individuals' worries suggests that changes in risk perception may mediate the relation between news coverage and risk attitudes.
Keywords: D80; D03; 330; media coverage; economic news; stability of risk attitudes; risk perception